Professor, Department of Nursing, Daewon University College, 316, Daehak-ro, Jecheon, 27135, Korea - Cho , Pyong-Kon; Jang, Hyon-Chol (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study was important to reduce genital radiation exposure during pediatric chest and breast X-ray, evaluate ease of a newly developed shielded apron, and helped parents and assistants monitor patient’s movements.Methods/Statistical analysis: If there are a various factors, such as pediatric patients, difficulty to accurately position due to the movement of the patient. To solve such problems, examinations are often conducted with the assistance of parents and helpers who control a patient’s movements during pediatric chest and breast X-ray examination. During the process, parents and helpers are unnecessarily exposed to radiation even though they wear aprons.Findings: This syudy, a newly developed shield was developed to prevent unnecessary radiation exposure by comparing the radiation dose associated with the use of gonad shield aprons in chest and breast X-ray of pediatrics patients. In this study, we use a newly developed shielding apron to shield the genitals during chest and breast X-ray and to reduce unnecessary radiation exposure to parents and helpers who control a patient’s movements during examinations.Improvements/Applications: Using a newly developed shield apron at chest and breast X-rays reduces genital radiation exposure and unnecessary radiation dosage for parents and helpers controlling pediatric patients movement.